Assessing aerodynamic influences on offshore foundation design for large wind farms - Wen, KZ; Dehtyriov, D; Byrne, BW (IOP Publishing, 2024)
An evaluation of the impact of aerodynamic interactions on offshore wind turbine (OWT) monopile design in large wind farms is presented. The interactions between turbines within a wind farm, and between the atmosphere and the entire wind-farm, act to reduce the mean effective loads across the farm. This reduction impacts the operational performance of OWT foundations in two notable ways: a decrease in turbine structural loads which affects design to serviceability limit state and a shift in excitation frequencies of the passing blades which impacts fatigue performance. To assess the implications on monopile design, we conduct static and dynamic analyses using a 1-D finite element model (FEM). We show that the farm-atmosphere interaction effect leads to marked reduction in monopile lengths between ∼ 5-25% across an entire wind farm. The dynamic analysis reveals a competing balance between shifting frequency bands and reduced wind loads on the fatigue response. The monopile design is found to be strongly dependent on wind farm size and ratio of wind to wave loading, with wave loading coupled to the farm-atmosphere interaction effect. Exploiting these interactions plays a pivotal role in reducing the levelised cost of wind energy and ensuring robust design of OWTs.